2020
DOI: 10.1038/s41598-020-61579-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of the PKR inhibitor C16 suppressing tumor proliferation and angiogenesis in hepatocellular carcinoma in vitro and in vivo

Abstract: The therapeutic effects of C16, which is an inhibitor of RNA-dependent protein kinase (PKR), on growth of hepatocellular carcinoma (HCC) cells and tumor progression in vitro and in vivo were evaluated. Huh7 cells, a human HCC cell line, were used. The effects of C16 on cell viability were evaluated with the MTT assay, and real-time RT-PCR was performed. Huh7 cells were grafted into immunodeficient mice, and the in vivo effects of C16 on tumorigenesis were examined. C16 suppressed proliferation of HCC cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Next, we tested the possible effect of other two viral dsRNA‐mediated innate antiviral mechanisms on shaping the transient phenotype of IVT‐CoV2‐Rep, specifically the PKR and oligoadenylate synthetase‐RNase L. 47 , 48 We first used compound C16, an inhibitor of PKR, 49 , 50 to treat the CHO‐K1 cells transfected with IVT‐CoV2‐Rep mRNA. The result demonstrated that C16 treatment increased replicon replication at day 1 posttransfection compared to DMSO control, but this pro‐viral effect disappeared quickly by Day 2 (Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we tested the possible effect of other two viral dsRNA‐mediated innate antiviral mechanisms on shaping the transient phenotype of IVT‐CoV2‐Rep, specifically the PKR and oligoadenylate synthetase‐RNase L. 47 , 48 We first used compound C16, an inhibitor of PKR, 49 , 50 to treat the CHO‐K1 cells transfected with IVT‐CoV2‐Rep mRNA. The result demonstrated that C16 treatment increased replicon replication at day 1 posttransfection compared to DMSO control, but this pro‐viral effect disappeared quickly by Day 2 (Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40] In light of the fact that IVT-CoV2-Rep does not encode viral structural and accessory proteins, we speculated that the transfected replicon RNA and/or replication intermediates might induce cellular innate immunity which eliminates replicon replication. However, it is also worth noting that among the above tested host cell lines, Huh7.5 possesses a mutationally inactivated RIG-I for IFN production, 41 Vero cells lack the IFN-β gene, 42,43 and BHK-21 cells have a compromised IFN induction and response, [44][45][46] 47,48 We first used compound C16, an inhibitor of PKR, 49,50 to treat the CHO-K1 cells transfected with IVT-CoV2-Rep mRNA. The result demonstrated that C16 treatment increased replicon replication at day 1 posttransfection compared to DMSO control, but this pro-viral effect disappeared quickly by Day 2 (Figure 5C).…”
Section: Transient Replicon Replication Is Not Due To Host Antiviral ...mentioning
confidence: 99%
“…C16 is a small molecule that can suppress the activation of PKR and prevents the translational block that follows PKR exposure (Jammi et al 2003, Shimazawa et al 2006). C16 has been extensively used to determine the role of PKR both in vivo (Xiao et al 2016) and in vitro (Watanabe et al 2020). The dose of C16 in this study was based on previous experience in which mice received C16 i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Among the nucleic acid sensors with direct antiviral action, PKR and ADAR have been implicated in HCC pathogenesis (142)(143)(144). A PKR inhibitor (C16) reduced cell division in Huh7 cells and markedly decreased liver tumor growth in a mouse model.…”
Section: Dysregulation Of Nucleic Acid-sensing Components Implicated ...mentioning
confidence: 99%
“…Moreover, it occurred that microvessel density of such tumors was decreased during PKR inhibition. Indeed, in vitro experiments revealed that angiogenesis-relevant growth factor expression-i.e., vascular endothelial growth factor A (VEGF-A), VEGF-B, platelet-derived growth factor A (PDGF-A), PDGF-B, fibroblast growth factor 2 (FGF-2), epidermal growth factor (EGF), and hepatocyte growth factor (HGF)-was significantly downregulated by PKR inhibition (142). These observations are in line with the results reported following analysis of a human HCC cohort (100% HCV-associated), showing increased activity of PKR in tumor samples as compared to cirrhotic tissues (143).…”
Section: Dysregulation Of Nucleic Acid-sensing Components Implicated ...mentioning
confidence: 99%